Pembangunan Dashboard Pusat Komando Armada Pada PT Indo Trans Teknologi - Arthur William, Brian; Hendrarini, Nina; Meisaroh, Lisda (eProceedings of Applied Science, 2024)
Along with the development of the transportation industry,the development of fleet dashboards has a crucial role inin influencing vehicle performance. With the presence ofdashboard, detailed vehicle condition data can be stored and processed for the company'sand processed for the benefit of the company, both inmonitoring, maintenance, and vehicle management. ByTherefore, the creation of an optimal dashboard is the main focus of the currentmain focus at this time. The dashboard created will integratevehicle data from various information sources, ensurereliability and consistency of the data, as well as adapting to the differentdiverse user needs. The use of dashboardsprovides several benefits for the company,among others, increasing operational efficiency, facilitatingstrategic decision-making, and supporting optimizedmonitoring for vehicle condition reports. Atdashboard creation at Kibana, the Scrum methodology was usedmethodology, which allows work to be done in small cyclesand incremental, ensuring that every part of the dashboard wasdeveloped with high quality and in accordance withuser needs. The result of the dashboard creationshow the accuracy of the data so that it can supportbetter decision-making, as well as ensuringoptimal vehicle condition monitoring. Keywords: Fleet, Dashboard, Kibana